Identifying risk factors for Jihadist terrorist offenders committing homicide: An explorative analysis using the European Database of Terrorist offenders - Alberda, Daphne L.; Duits, Nils; van den Bos, Kees; Autsema, Anneke; Kempes, Maaike (Frontiers in Psychology, 2022)
Although many studies have examined various aspects of terrorism, relatively little is known about risk indicators associated with specific types of terrorist offences. To partly fill this void, this study explores differences on risk indicators of the Violent Extremism Risk Assessment tool (VERA-2R) between 21 Jihadist offenders who were convicted for homicide and a comparison group of 30 Jihadist offenders convicted for other Jihadist terrorist offences. In doing so, we use judicial data from the European Database of Terrorist offenders (EDT). The results reveal that a number of risk and protective indicators differ between both groups. Both terrorist offender groups often expressed grievances about perceived injustice, but the homicide group more frequently expressed anger, moral outrage, or hatred in response to the perceived injustice than the comparison group. The homicide group also identified their attacks more often than the comparison group, and were more actively engaged in planning and preparation them. Additionally, the homicide group was less often motivated to commit their terrorist offences by group belonging compared with the non-homicide group. With respect to the protective indicators, persons in the comparison group more often reject violence as a means to achieve goals. Although further research is necessary, the results from this study indicate that a differentiated approach might be needed for risk assessment and risk management of the terrorist offender population.